The Impact of Coal, Nickel, and Crude Oil Prices on the Composite Stock Price Index 2020-2023 - Fadlih Ramdan (Politeknik Siber Cerdika Internasional, 2024)
Several elements can impact stock prices on the Indonesia Stock Exchange (IDX). A key factor is the variation in prices of coal, nickel, and crude oil, which is significant due to the considerable market capitalization of this sector in Indonesia. This study aims to assess the influence of coal, nickel, and crude oil prices on the Jakarta Composite Index (JCI). The research utilizes quantitative data, specifically secondary data sources. The data analysis covers a monthly period from 2020 to 2023, with multiple regression analysis employed as the technique. The study's outcomes indicate a notable effect of nickel and crude oil prices on the JCI from 2020 to 2023